Selective Csp3–F Bond Functionalization with Lithium Iodide - Balaraman, Kaluvu; Kyriazakos, Samantha; Palmer, Rachel; Thanzeel, F. Yushra; Wolf, Christian (Synthesis, 2022)
A highly efficient method for C–F bond functionalization of a broad variety of activated and unactivated aliphatic substrates with inexpensive lithium iodide is presented. Primary, secondary, tertiary, benzylic, propargylic and α-functionalized alkyl fluorides react in chlorinated or aromatic solvents at room temperature or upon heating to give the corresponding iodides, which are isolated in 91–99% yield. The reaction is selective for aliphatic monofluorides and can be coupled with in situ nucleophilic iodide replacements to install carbon–carbon, carbon–nitrogen, and carbon–sulfur bonds with high yields. Alkyl difluorides, trifluorides, even in activated benzylic positions, are inert under the same conditions and aryl fluoride bonds are also tolerated.
Keywords: C–F bond functionalization; alkyl fluorides; halide exchange; nucleophilic substitution; lithium iodide